2003
DOI: 10.1016/s0022-5223(03)01297-2
|View full text |Cite
|
Sign up to set email alerts
|

Intralobar sequestration in the middle-aged and elderly adult: recognition and radiographic evaluation

Abstract: Intralobar sequestration is a rare cause of recurrent bronchitis, pneumonia, or hemoptysis that is often misdiagnosed both because of a lack of recognition of radiologic findings and a low expectation of the disease, particularly in middle-aged and elderly adults. Definitive therapy is surgical, and preoperative delineation of anatomy is essential. We present 2 cases from our institution that were atypical in presentation and used different radiographic imaging modalities. A review of the literature pertaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 18 publications
2
46
0
4
Order By: Relevance
“…Intralobar sequestration has almost equal gender prevalence. [9] In the current study, distribution between the genders was equal as reported in literature.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Intralobar sequestration has almost equal gender prevalence. [9] In the current study, distribution between the genders was equal as reported in literature.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast to extralobar sequestration, intralobar sequestration is infrequently associated with other congenital abnormalities. [9] Halkic et al [10] stated that ILS often remains unrecognized until after the age of 20. The current study data support this statement with the mean age of 33.3±13.7 years (range 4 to 61 years) at diagnosis for ILS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Широкое распростра нение компьютерной томографии (КТ) позволяет чаще диагностировать эту патологию и выделять ее в структуре острых и хронических неспецифических заболеваний легких [3,4]. Традиционное хирурги ческое лечение заключается в перевязке аномально го сосуда и удалении пораженной части легкого, осу ществляемое путем открытых вмешательств [5,6].…”
Section: заметки из практикиunclassified
“…Among the two types of BPS, intralobar BPS is more common, representing approximately 75∼90% of BPS 2,7 . Intralobar BPS is diagnosed in the second decade of life or younger in approximately 50∼60% of cases, and rarely found in patients older than 50 years 6 . As the patient reported here, most senile patients experience chronic cough, sputum, and recurrent attacks of pneumonia similarly with juvenile patients 8 .…”
Section: Case Reportmentioning
confidence: 99%
“…Intralobar sequestration is typically diagnosed in pediatric or adolescent patients, with equal gender prevalence. These are rarely found in patients older than 50 years 6 . Most intralobar BPSs are supplied with arterial blood by the thoracic or abdominal aorta 2 .…”
Section: Introductionmentioning
confidence: 97%